Fusarium spp. and levels of fumonisins in maize produced by subsistence farmers in South Africa - Edson Ncube; Bradley Flett; Cees Waalwijk; Altus Viljoen (South African Journal of Science)
Fusarium spp. produce fumonisins - mycotoxins that are of importance to maize production in South Africa. Fumonisins have been associated with human oesophageal cancer and cause various diseases in animals that are of concern to the animal feed industry. Maize samples, collected from subsistence farm fields in the Eastern Cape, KwaZulu-Natal, Limpopo and Mpumalanga provinces of South Africa during the 2006 and 2007 growing seasons, were analysed for Fusarium spp. and contamination with fumonisins. Fusarium verticillioides was the most common Fusarium species in maize followed by F. subglutinans and F. proliferatum. Levels of contamination with fumonisins ranged from 0 Î¼g/g to 21.8 Î¼g/g, depending on the region where samples were collected. Levels of fumonisins were highest in northern KwaZulu-Natal (Zululand) where 52% and 17% of samples collected in 2006 and 2007, respectively, exceeded 2 Î¼g/g. Regression analyses showed a positive correlation between fumonisin-producing Fusarium spp. determined by real-time polymerase chain reaction and concentration of fumonisins (r = 0.93). Many samples from Zululand, and some from Mokopane (Limpopo) and Lusikisiki (Eastern Cape), contained fumonisins at levels well above the maximum levels of 2 Î¼g/g set by the Food and Drug administration (USA) and therefore also the limit of 1 Î¼g/g set by the European Union for food intended for direct human consumption. Regulations governing contamination of grain with fumonisins are not yet implemented in South Africa. The high incidence of fumonisins in subsistence farming systems indicates the need for awareness programmes and further research.